Breast cancer in North-Central Nigeria: challenges to good management outcome - Umoke, Ifeanyi Charles; Garba, Ekundayo Stephen (International Surgery Journal, 2019)
Background: Breast cancer is a major health burden globally. Now ranked the number one cancer in females, and the leading cause of cancer deaths in females in our environment, outcome indices have remained poor in developing countries. The aim of this study was to ascertain the major challenges to good management outcome of breast cancer patients in our centre. Methods: The case notes of all histologically confirmed cases of breast cancer presenting to our centre from January 2016 to December 2017 were reviewed. Information on the variables of interest were extracted using a proforma. Results: Fifty-five (55) patients’ case notes were reviewed. All were females. 30.9% of the patients had early disease versus 67.3% with advanced disease. 76.4% had invasive ductal carcinoma. More lesions occurred on the left and the upper outer quadrants. 46% of the 37 patients with advanced disease who required chemotherapy completed the prescribed six courses. None of the patients who required radiotherapy received it. Only 1.8% of those who required hormonal therapy were still taking them at two years follow-up. 3.6%, 11%, and 0% used alcohol, oral contraceptives and tobacco respectively. 81.8% had been lost to follow-up at two years while 14.5% had died while on admission. Conclusions: This study identified late presentation with advanced disease; poor compliance and adherence to treatment strategies, and poor access to adjuvant therapy as the major challenges to good outcome for this disease.